Aqueous Suzuki–Miyaura Coupling with Ultralow Palladium Loading and Simple Product Separation - Yang, Wei; Xu, Wen-Di; Ning, Jin-Jiao; Ren, Zhi-Gang; Young, David James (Synlett, 2020)
The diphosphine ligand N,N-bis(diphenylphosphanylmethyl)-aniline (bdppma) and PdCl2 afforded a Suzuki–Miyaura catalyst [(bdppma)PdCl2] that was highly efficient at an ultralow catalyst loading (0.001 mol%) in 20:1 H2O–EtOH. This low catalyst loading in an aqueous solvent system permitted simple product separation by direct filtration without the need for chromatography. The ligand bdppma imparted surprisingly better reactivity than that achieved with other bidentate diphosphine ligands, but the catalytic system had a slightly narrower substrate scope than some similar Pd catalysts reported previously.
Keywords: Suzuki–Miyaura reaction; palladium catalysis; ligands; aryl bromides; arylboronic acids; biaryls